MITIGATING CORPORATE FAILURES IN LISTED CONSUMER GOODS FIRMS: THE INFLUENCE OF AUDIT FIRM ATTRIBUTES IN NIGERIA - Chukwudi , Emeka Okonkwo (Research Journal of Economics and Sustainable Development, 2024)
The study examined audit firm physiognomies as a contrivance for mitigating corporate failures in listed consumer goods firms in Nigeria. The specific objective of the study was to ascertain the extent to which audit fee, audit firm size and audit firm tenure help to prevent the likelihood of corporate failure. The likelihood of corporate failure was measured using Altman’s Z-score framework. The study employed an ex-post facto research design. All twenty-one firms listed under the consumer goods sector of the Nigerian Exchange Group comprised the population of the study. The study utilized purposive sampling to select 16 firms that made up the sample size. Secondary data were sourced from the audited financial statements and annual reports of the firms over a 10 year period, from 2012 to the 2021. In addition to the descriptive analysis, the study employed ordinary regression method to test the hypotheses. The findings revealed that: larger audit fee significantly helps to mitigate the likelihood of corporate failure (p-value = 0.0000); larger audit firm size significantly helps to mitigate the likelihood of corporate failure (p-value = 0.0036); but higher audit firm tenure worsens the likelihood of corporate failure although this effect is not significant (p-value = 0.0923). In conclusion, a high-quality audit can help companies to identify potential risks and take necessary measures to mitigate them, thereby reducing the likelihood of financial distress. The study recommends that firms in Nigeria should consider investing in high-quality audits, even if it means incurring higher audit fees which can help to enhance the accuracy and credibility of their financial statements, thereby fostering greater investor confidence and securing longterm financial stability.